WordPress for dummies - Sabin-Wilson, Lisa (--For dummies., 2011)
Discover the wonders of WordPress and learn easy ways to power up your blog. Sabin-Wilson walks you through the process, from setting up WordPress and choosing themes, to using Wordpress as a CMS to create a full website.